FAKTOR YANG MEMENGARUHI KEPUASAN KERJA PERAWAT DI RUMAH SAKIT: LITERATURE REVIEW - Ribut Fitnanto; Tina Shinta Parulian; Elizabeth Ari Setyarini (STIKes Santa Elisabeth Medan, 2021)
Abstract The background of this study are there are 41% of hospital nurses expereinced dissatisfaction with their jobs and 22% among them planning to leave their job in one year. Job satisfaction is a form of people perception reflected in attitude and focused on job behaviour. The aim of this study is to identified factors that affect hospital nurses’ job satisfaction. The articles used in this study are between the years of 2011-2021 from PubMed, Research Gate, and Scholar with PICO format. Seventeen articles are chosen to be analyzed. This study shows that most of the hospital nurses aren’t satisfied with their jobs. Factors that affecting job satisfaction are motivation factors including; achievement, job, promotion, motivation, and safety factor; and hygiene factors including; salary, supervisor, partner, and environment factor. Hospital should make SOP about salaryprocessing, supervisor selection, equal job distribution based on job partner, awards for nurses, motivation, and opportunity to gain promotion and work safety guarantee.